HASIL BELAJAR MAHASISWA TERHADAP HUBUNGAN INTERPERSONAL - Vivin Ayu Dwi L (Pendidikan Ekonomi, 2013)
Communication is a means of interaction and connecting people. Besides, communication has an important role in human life since human is a social creature. It means, as the social creature, human cannot live alone and will always interact with the other. Communication is one of the sciences that can be learnt in field of study. This field of study had already learnt and applied by the Education Administration Office students of Economics Faculty of Surabaya State University. From the learning process, the students got good learning outcomes to support the interpersonal relationship. This study aims to find out the effect of learning outcomes on Communication science subject toward the interpersonal relationship among the students of Education Administration Office year 2008. The sample used is the saturated Sample those are all of the students of Education Administration Office year 2008. The data gathering technique are observation, documentation and questionnaire. The data analysis technique is Classical Assumption Test and a simple linear regression. The Kolmogorov Smirnov test result normal distributed data and linear. The result of the study showed partially that there are no significant effects between the Communication science subject and the interpersonal relationship.